(untitled) (Journal of Kidney Cancer, 2024)
Adenoid cystic carcinoma (ACC) is a rare tumor, accounting for 1% of all head and neck cancers, with an aggressive nature characterized by local recurrence, delayed metastasis, and survival of less than 50% at 10 years. This is a case of biopsy-proven ACC to the kidney, 1 of 29 known occurrences, managed by metastasectomy by robotic-assisted nephrectomy, with plans for resection of lung metastasis. Thirteen years after diagnosis of sinonasal ACC treated with resection, the patient presented with shortness of breath. This prompted a CT scan of the chest, which led to the incidental finding of left renal mass and pulmonary lesion. Literature suggests improved disease-specific survival in locoregional recurrence treated with surgery versus radiation; in patients with metastasis to the lung, metastasectomy offers greater survival benefit than supportive therapy. But, this is not significantly better than chemotherapy or radiation alone. While the optimal therapeutic approach remains to be identified in distant metastatic ACC, metastasectomy remains a viable option for patients who have potentially completely resectable metastatic tumors, appropriate performance status, and adequate affected-organ function. Preoperative counseling should include discussion on partial nephrectomy with prioritization of nephron-sparing but potential for increased perioperative risk versus radical nephrectomy to ensure negative margins and expedite timeline to systemic therapy.